Can Opacity of a Credible Central Bank Explain Excessive Inflation? - Romain Baeriswyl; Camille Cornand (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2007)
Excessive inflation is usually attributed to the lack of central bank's credibility. In this context, most of the literature considers transparency a means to establish central bank's credibility. The contribution of this paper is twofold. First, it shows that, even in the absence of inflationary bias, a credible central bank may find it optimal to implement an accommodating monetary policy in response to cost-push shocks whenever the uncertainty surrounding its monetary instrument is high. Indeed, the degree of central bank's transparency influences the effectiveness of its policy to stabilize inflation in terms of output gap, and thereby whether it will implement an expansionary or contractionary policy in response to cost-push shocks. Second, it stresses that transparency is not just a means to achieve credibility but is essential per se for the optimality of monetary policy of a fully credible central bank.
urn:nbn:de:bvb:19-epub-1376-3
Keywords: E58; E52; D82; 330; monetary policy; differential information; transparency; cost-push shocks; Inflation; Kreditwürdigkeit; Geldpolitik; Zentralbank; Theorie